Características de personalidad asociados al consumo virtual de contenido sexual en personas entre 20 y 50 años de edad en la ciudad de Cartago (2022)
The present research aimed to analyze the personality components associated with virtual consumption of sexual content in people between 20 and 50 years old in the city of Cartago, the methodology used for this study was quantitative design no experimental cross-section with descriptive scope and analytical empirical criteria.